Enterprise Sustainability: Literature Review in the Context of SMEs Worldwide - Fuentes Doria, Deivi David; Toscano Hernández, Aníbal Enrique; Sepúlveda Vargas, Rubén Darío (Opción, 2020)
This paper presents the results of a study seeking to identify the main features of worldwide scientific scholarly publications in the field of enterprise sustainability but more specifically, in the area of small and medium enterprises (SMEs). We applied a mixed quantitative-qualitative method for the identification and analysis of writings on principles of sustainability, sustainable enterprise management, and sustainable development. Scientific scholarly journals, books, and reviews were indexed at Scopus Database and being devoted to the field of small and medium enterprises (SMEs), served as primary sources for this study. Historic content, as well as abstracts, co-authorship, titles, and other keywords were further elements restricting this review Abstrac This paper presents the results of a study seeking to identify the main features of worldwide scientific scholarly publications in the field of enterprise sustainability but more specifically, in the area of small and medium enterprises (SMEs). We applied a mixed quantitative-qualitative method for the identification and analysis of writings on principles of sustainability, sustainable enterprise management, and sustainable development. Scientific scholarly journals, books, and reviews were indexed at Scopus Database and being devoted to the field of small and medium enterprises (SMEs), served as primary sources for this study. Historic content, as well as abstracts, co-authorship, titles, and other keywords were further elements restricting this review.